Beyond ‘Earlygold’: Juice Color and Quality of Additional Early-Maturing Sweet Orange Selections - William S. Castle (EDIS)
This publication summarizes 5 years of juice quality information about 15 early-maturing sweet orange selections introduced to Florida and evaluated after ‘Earlygold’ became available. The trees were grown at a central Florida and Indian River location for about 10 years. Also presented are observations on tree development summarized across both locations and two rootstocks. This 8-page fact sheet was written by William S. Castle and published by the UF Department of Horticultural Sciences, January 2013.